2021
DOI: 10.1177/23259671211023098
|View full text |Cite
|
Sign up to set email alerts
|

Adductor Muscle Injuries in UEFA Soccer Athletes: A Matched-Cohort Analysis of Injury Rate, Return to Play, and Player Performance From 2000 to 2015

Abstract: Background: The effects of adductor muscle injury on performance in soccer athletes are unknown. Purpose: To (1) determine the rate and time to return to play (RTP) after adductor muscle injury, (2) investigate the rate of reinjury after RTP, and (3) investigate any long-term effects of injury on elite soccer player performance. Study Design: Cohort study; Level of evidence, 3. Methods: Using publicly available records, athletes sustaining adductor muscle injury were identified across the 5 major European socc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The majority of the findings in the present study are aligned with those reported in professional football players: data related to overall injuries as well as to hamstrings, quadriceps, and calf muscles injuries are similar to those previously reported for adult players [ 2 , 10 , 11 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…The majority of the findings in the present study are aligned with those reported in professional football players: data related to overall injuries as well as to hamstrings, quadriceps, and calf muscles injuries are similar to those previously reported for adult players [ 2 , 10 , 11 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…In soccer players, abnormal technical movements and structural asymmetries post anterior cruciate ligament reconstruction (4, 13) have been proposed as risk factors for adductor muscle injuries (up to 63% in soccer) (18) and groin pain. During rehabilitation process, a gradual and progressive re-introduction of kicking load of basic technical skills is considered a dogma of clinical reasoning (19).…”
Section: Discussionmentioning
confidence: 99%
“…The strength expressions of the adductors and the range of motion of the hip have received particular scientific interest due to the repetitiveness of soccer gestures. Studies (18,26) have shown injuries to the adductor and quadriceps muscles in the dominant/kicking limb compared to the non-dominant leg. Bi-articular muscles, with a prevalence of type II muscle fibres (rectus femoris approx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because a high caseload of injuries in elite athletes is uncommon in the clinical setting, the use of public sources of information is a common practice in research aimed at assessing the consequences of injuries in this population [ 2 , 4 , 5 , 8 , 19 , 20 , 24 , 29 , 31 ]. Transfermarkt.com is a particularly noteworthy source, and while it is primarily aimed at reporting club transfers, it also contains pertinent data for clinical and sports analytics, such as injury reports, match outcomes, and player match participation data [ 30 ].…”
Section: Introductionmentioning
confidence: 99%